2005
DOI: 10.1002/ana.20394
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor returning in complex regional pain syndrome parallels pain reduction

Abstract: Patients with complex regional pain syndrome (CRPS) and intractable pain showed a shrinkage of cortical maps on primary (SI) and secondary somatosensory cortex (SII) contralateral to the affected limb. This was paralleled by an impairment of the two-point discrimination thresholds. Behavioral treatment over 1 to 6 months consisting of graded sensorimotor retuning led to a persistent decrease in pain intensity, which was accompanied by a restoration of the impaired tactile discrimination and regaining of cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
208
2
22

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 346 publications
(239 citation statements)
references
References 17 publications
7
208
2
22
Order By: Relevance
“…In a study of patients with complex regional pain syndrome (CRPS), a sensorimotor training program was shown to lead to pain reduction and improvement of tactile discrimination as well as restoration of activation patterns in primary and secondary somatosensory cortices (63). This confirms earlier MEG studies (64), which had suggested that reversal of somatosensory cortex reorganization might be a useful marker of treatment efficacy in disease entities in which impaired sensorimotor circuits might play an important role in the generation of pain (64,65).…”
Section: Application Of Phfmri To Pain Researchsupporting
confidence: 66%
“…In a study of patients with complex regional pain syndrome (CRPS), a sensorimotor training program was shown to lead to pain reduction and improvement of tactile discrimination as well as restoration of activation patterns in primary and secondary somatosensory cortices (63). This confirms earlier MEG studies (64), which had suggested that reversal of somatosensory cortex reorganization might be a useful marker of treatment efficacy in disease entities in which impaired sensorimotor circuits might play an important role in the generation of pain (64,65).…”
Section: Application Of Phfmri To Pain Researchsupporting
confidence: 66%
“…Cortical reorganisation in regions associated with the body schema (i.e. primary somatosensory cortex, posterior parietal lobe) have been revealed by brain imaging, providing further evidence of body schema disruption [27,28,29,34].…”
Section: Introduction "If the Pain Is Very Intense Even If I Am Toucmentioning
confidence: 90%
“…Two participants also depicted distortions of the unaffected side. As there was no known CRPS pathology of the unaffected side, these distortions could possibly be explained by altered central processing within cortical centres responsible for limb representation as demonstrated by brain imaging studies [25,27,28,34]. It is acknowledged that this unvalidated measure was devised specifically for this study hence these results are exploratory.…”
Section: Upper Limb Position and Mental Representation Of The Limbmentioning
confidence: 99%
“…For example shrinkage in cortical representation of the affected limb is known to occur within the primary somatosensory cortex (SI) (Juottonen et al 2002;Maihofner et al 2003;Maihofner et al 2004;Pleger et al 2005;Pleger et al 2006). SI is responsible for processing tactile inputs and provides a central somatosensory representation of the body surface.…”
Section: Disturbances In Body Perceptionmentioning
confidence: 99%
“…The extent of cortical alterations relate to the degree of pain (Maihofner et al 2004). Importantly, aberrant mapping reverses as pain diminishes (Maihofner et al 2004;Pleger et al 2005). In light of this, it is unsurprising that pain seems to have a detrimental influence on thoughts, feelings and how individuals perceive their affected body part (Lewis et al 2007;Lewis et al 2010).…”
Section: Disturbances In Body Perceptionmentioning
confidence: 99%